Active Acoustic Surfaces Enable the Propulsion of a Wireless Robot. Issue 21 (29th September 2017) - Qiu, Tian; Palagi, Stefano; Mark, Andrew G.; Melde, Kai; Adams, Fabian; Fischer, Peer
Abstract: A major challenge that prevents the miniaturization of mechanically actuated systems is the lack of suitable methods that permit the efficient transfer of power to small scales. Acoustic energy holds great potential, as it is wireless, penetrates deep into biological tissues, and the mechanical vibrations can be directly converted into directional forces. Recently, active acoustic surfaces are developed that consist of 2D arrays of microcavities holding microbubbles that can be excited with an external acoustic field. At resonance, the surfaces give rise to acoustic streaming and thus provide a highly directional propulsive force. Here, this study advances these wireless surface actuators by studying their force output as the size of the bubble‐array is increased. In particular, a general method is reported to dramatically improve the propulsive force, demonstrating that the surface actuators are actually able to propel centimeter‐scale devices. To prove the flexibility of the functional surfaces as wireless ready‐to‐attach actuator, a mobile mini‐robot capable of propulsion in water along multiple directions is presented. This work paves the way toward effectively exploiting acoustic surfaces as a novel wireless actuation scheme at small scales. Abstract : Acoustic active surfaces are developed based on 2D arrays of acoustically resonant microbubbles, which provide highly directional propulsive forces in fluids through acoustic streaming. The surfaces are remotely powered by an external acoustic field and can be directly attached to passive devices to provide wirelessly addressable mechanical forces with multiple degrees of freedom.